2014
DOI: 10.1371/journal.pone.0097080
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Involved in Prostate Gland Adaptation to Androgen Deprivation

Abstract: Androgens regulate prostate physiology, and exert their effects through the androgen receptor. We hypothesized that androgen deprivation needs additional transcription factors to orchestrate the changes taking place in the gland after castration and for the adaptation of the epithelial cells to the androgen-deprived environment, ultimately contributing to the origin of castration-resistant prostate cancer. This study was undertaken to identify transcription factors that regulate gene expression after androgen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…These diverse functions depend on poorly understood, complex gene expression networks and cell‐cell interactions. Accordingly, we have found that some genes escape the simplistic on‐or‐off expression pattern of androgen‐regulation via the androgen receptor (Rosa‐Ribeiro & Nishan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These diverse functions depend on poorly understood, complex gene expression networks and cell‐cell interactions. Accordingly, we have found that some genes escape the simplistic on‐or‐off expression pattern of androgen‐regulation via the androgen receptor (Rosa‐Ribeiro & Nishan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that the NFκB pathway might be implicated in the post‐castration behavior of the epithelium and contributes to desquamation is consistent with the modulation of NFκB family members after androgen deprivation (Rosa‐Ribeiro et al, ), but remains to be proven.…”
Section: Desquamation Atrophy and Proliferative Inflammatory Atrophmentioning
confidence: 76%
“…No TUNEL positivity was found in sections of the VK3/AAtreated tumours, suggesting that the reduction in tumour size induced by VK3/AA was due to tumour growth inhibition rather than induction of cell death. This was corroborated by the fact that at prolonged time of exposure to the drugs (days [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], the tumours re-started to grow. Treatment with -TOS/VK3/AA significantly inhibited tumour growth (days 43-49, p = 0.04), inducing wide areas of cell death associated with AIF nuclear translocation, as compared to the control animals and those treated with the individual drugs.…”
Section: Redox-active and Redox-silent Compounds Exert Different Modementioning
confidence: 89%
“…Cells activate pathways in response to oxidative stress that promotes cell survival and adaptation [42,43]. The mechanism of cancer cell redox adaptation may involve multiple pathways to activate redox-sensitive transcription factors such as NF-B or the nuclear factor erythroid 2-related factor 2 (Nrf-2) [44,45] that can lead to increased expression of antioxidants such as SOD, CAT, and thioredoxin, and the GSH system. Under normal conditions, Nrf2 is targeted for proteasomal degradation by Kelch-like ECH-associated inhibitor protein-1 (Keap1).…”
Section: Cellular Response To Oxidative Stress: Cell-death and Survivmentioning
confidence: 99%